Paranormal beliefs of preservice teachers' - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
The purpose of this study was to investigate pre-service teachers' attitudes towards paranormal beliefs. In this study whether pre-service teachers' attitudes towards paranormal beliefs changed in terms of their programme and gender was examined. The data was collected during the fall semester of the 2010-2011 academic year. The research sample was 236 pre-service teachers in a four year teacher preparation programme at Mersin University in Turkey. Data related to pre-service teachers' attitudes towards paranormal beliefs was collected through the Revised Paranormal Scale. Pre-service teachers' responses to the scale were the major data for this study. The statistical analysis of the data was carried out by means of SPSS 11 for Windows. (c) 2011 Published by Elsevier Ltd. Open access under CC BY-NC-ND license.
Keywords: Education; Paranormal Beliefs; Preservice teachers